Mednarodni eTwinning projekt na Osnovni šoli Prule z naslovom Who are you? - Škrlj, Gregor (Šolska knjižnica, 2016)
In the 2014/2015 school year, we decided to join an international project under eTwinning. It all began when we attended a contact seminar for participating schools. Before the new school year started, during summer holidays, we had prepared a plan, a yearly lesson plan and an online classroom, and had become involved in all of the project's online environments. We wished to provide students with an alternative learning method using information and communication technology (ICT), the learning of foreign languages, and meeting their peers from other countries. At the end of the project we established that the learning and socialising had been invaluable, and that the participating students had made new friends and learnt many new things.
Keywords: eTwinning; IKT; informacijsko-komunikacijska tehnologija; mednarodni projekti; motivacija; šolske knjižnice; tuji jeziki; učne metode